2020
DOI: 10.1007/s13300-020-00948-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Lobeglitazone Versus Pioglitazone on Albuminuria in Patients with Type 2 Diabetes Mellitus

Abstract: Introduction: The aim of this analysis was to evaluate the efficacy of lobeglitazone on albuminuria at 24 weeks of follow-up in patients with type 2 diabetes mellitus (T2DM) compared with pioglitazone using data from a randomized, double-blinded phase III trial. Methods: In the phase III trial, patients who were inadequately controlled with metformin Kyung-Soo Kim and Sangmo Hong contributed equally to the work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…A randomized controlled trial (RCT) conducted by Kim et al on albuminuria in patients with type 2 diabetes concluded that lobeglitazone improved albuminuria in patients with type 2 diabetes as measured by the urinary albumin-creatinine ratio (UACR), and demonstrated it as beneficial. In the lobeglitazone treatment group, the new onset of microalbuminuria was reduced by 73%, the progression of albuminuria was reduced by 52%, and there was no significant difference with the pioglitazone treatment group [3].…”
Section: Albuminuriamentioning
confidence: 83%
See 1 more Smart Citation
“…A randomized controlled trial (RCT) conducted by Kim et al on albuminuria in patients with type 2 diabetes concluded that lobeglitazone improved albuminuria in patients with type 2 diabetes as measured by the urinary albumin-creatinine ratio (UACR), and demonstrated it as beneficial. In the lobeglitazone treatment group, the new onset of microalbuminuria was reduced by 73%, the progression of albuminuria was reduced by 52%, and there was no significant difference with the pioglitazone treatment group [3].…”
Section: Albuminuriamentioning
confidence: 83%
“…Some Asian countries such as Korea and India have approved the use of lobeglitazone for the treatment of T2DM. It was invented and approved in Korea [3]. Pioglitazone has a positive impact on lipid profiles in T2DM patients.…”
Section: Introductionmentioning
confidence: 99%
“…Along with its glucose‐lowering and lipid‐modifying effects, lobeglitazone has beneficial effects on beta‐cell function and survival 24‐26 . A recent study has shown that lobeglitazone may improve albuminuria in patients with T2DM 27 . Similar to other oral antidiabetic agents, lobeglitazone is effective as monotherapy and combination therapy 25,28,29 …”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] A recent study has shown that lobeglitazone may improve albuminuria in patients with T2DM. 27 Similar to other oral antidiabetic agents, lobeglitazone is effective as monotherapy and combination therapy. 25,28,29 In this study, we aimed to evaluate the efficacy and safety of lowdose (0.25 mg/day) lobeglitazone compared with standard-dose (0.5 mg/day) lobeglitazone in patients with T2DM and poor glucose control despite combination treatment with metformin and DPP4 inhibitor we often encounter in clinical practice.…”
Section: Introductionmentioning
confidence: 99%